Characterization of cellulose and other exopolysaccharides produced from Gluconacetobacter strains. (22nd January 2015) - Fang, Lin; Catchmark, Jeffrey M.
Highlights: Structural and morphological characterization of cellulose and non-cellulosic EPS produced by four Gluconacetobacter strains was performed in this study under the influence of different carbon sources. Gluconacetobacter xylinus ATCC 23769 could serve as a good model system for cellulose synthesis and interaction with other polymers because it does not produce any significant amount of water-soluble EPS. A distinct alkaline stable crystalline product was produced from Gluconacetobacter xylinus ATCC 53524 and ATCC 700178 when galactose served as the exclusive carbon source. Abstract: This study characterized the cellulosic and non-cellulosic exopolysaccharides (EPS) produced by four Gluconacetobacter strains. The yields of bacterial cellulose and water-soluble polysaccharides were dependent on both carbon source and Gluconacetobacter strain. The carbon substrate also affected the composition of the free EPS. When galactose served as an exclusive carbon source, Gluconacetobacter xylinus ( G. xylinus ) ATCC 53524 and ATCC 700178 produced a distinct alkaline stable crystalline product, which influenced the crystallization of cellulose. Gluconacetobacter hansenii ( G. hansenii ) ATCC 23769 and ATCC 53582, however, did not exhibit any significant change in cellulose crystal properties when galactose was used as the carbon source. Microscopic observation further confirmed significant incorporation of EPS into the cellulose composites. The cellulosic network produced from galactose medium showed distinctive morphological and structural features compared to that from glucose medium.